2019
DOI: 10.3390/polym11101697
|View full text |Cite
|
Sign up to set email alerts
|

Durable Antipilling Modification of Cotton Fabric with Chloropyrimidine Compounds

Abstract: Cotton fabric, a natural cellulose material, is widely used in the textile industry for its excellent properties. However, its application in some fields are seriously restricted because of its poor antipilling behavior. In this study, cotton fabrics were modified with 2,4,6-trichloropyrimidine (TLP), 2,4-dichloro-5-methoxypyrimidine (DMP), and 2-amino-4,6-dichloropyridine (ADP). The surface morphology and chemical structure of the modified cotton fabric were characterized by scanning electron microscopy (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It could be seen from Table 2 that compared with the raw cotton fabric, the crystallinities of the dyed cotton fabrics were changed approximately ±3%, indicating that dyeing processes had little effect for the crystallinity. XRD results showed that the direct, mordant and cross-linked dyeing mainly occurred on the active surface or amorphous areas, and retained the original crystal of the cotton fabrics [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…It could be seen from Table 2 that compared with the raw cotton fabric, the crystallinities of the dyed cotton fabrics were changed approximately ±3%, indicating that dyeing processes had little effect for the crystallinity. XRD results showed that the direct, mordant and cross-linked dyeing mainly occurred on the active surface or amorphous areas, and retained the original crystal of the cotton fabrics [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The maximum decomposition state was observed in the range of 250 ˚C to 350 ˚C. This corresponded to the decomposition of the cotton cellulose chain into small molecules as shown in figure 5 [14]. In this range, the weight loss was 62.49%, 64.39%, 63.24%, 60.87%, and 57.13% for P/C, I1, I2, I3, and I4, respectively.…”
Section: Synthesis and Characterization Of Fe-ta Npsmentioning
confidence: 87%
“…After cooling, the metal capsules with the paint fleets were removed from the installation. The dyed samples were washed repeatedly with warm water and cold water and finally rinsed for 15-20 min with 60-70 mL of distilled water, at 80 • C, to completely remove the dye not fixed on the textile fabric [20].…”
Section: Methodsmentioning
confidence: 99%